DECOLONIZING ARCHITECTURAL EDUCATION: PERSPECTIVES FROM THE GLOBAL SOUTH - Bandeira, Fernanda Brito; Scarazzato, Paulo Sergio (Seven Editora, 2025)
The critical review of The Routledge Companion to Architectural Pedagogies of the Global South examines the work edited by Harriss, Salama, and Lara (2022), which compiles 34 chapters across four sections, challenging architectural canons of the Global North. The book recenters Global South pedagogies, promoting marginalized voices and themes such as postcolonialism, spatial justice, and climate apartheid. Section I explores theoretical tools for South-South/North-South engagement; Section II questions imported curricula, proposing community co-creation; Section III highlights the political nature of pedagogy; and Section IV focuses on hybrid hermeneutics. Despite its representativeness (52% women, 28% Black/Brown) and diverse perspectives, its publication in English limits access. The work is essential for decolonizing curricula and resonating with university debates. It is recommended for inclusive pedagogical reforms.DOI: https://doi.org/10.56238/sevened2025.030-036